Spenser’s Method of Grace in the Legends of Holiness, Temperance, and Chastity - Miller, Rachel A. (My University, 2020)
The knights Redcrosse, Guyon, and Scudamour from The Faerie Queene are tasked with quests that curiously do not depend on wit or strength. Rather, the quests depend on each knight’s virtue and his acceptance of grace, the supreme virtue for Spenser. Through the wanderings of each knight, Spenser shows that there is a method of grace fashioned specifically for each knight’s quest both physical and spiritual that always requires the knights to reject false images of grace in exchange for God’s true grace. Grace will not abandon Gloriana’s knights, but as Guyon and Scudamour’s stubborn rejection of this virtue teaches, when grace is rejected, divine harmony, the loving cooperation between God and humanity that Redcrosse glimpses at the end of his quest, will be broken and replaced with fear and all the vices that follow it. Keyword 1: The Faerie Queene -- Keyword 2: Arthurian Literature -- Keyword 3: Theology -- Keyword 4: Edmund Spenser -- Keyword 5: Grace -- Keyword 6: Renaissance Literature
Chapter I: INTRODUCTION 1 -- Spenser’s World: The Faerie Queene’s Historical Context 2 -- Chapter 2: WHEN A CLOWNISH YOUNG MAN SLAYS A DRAGON 13 -- Redcrosse Receives His Calling 13 -- Discovering Truth 16 -- Discovering Faith 22 -- Discovering Grace 29 -- Paradise Regained 36 -- Chapter 3: WHEN A CAUTIOUS KNIGHT SAVES A GARDEN 41 -- Guyon Receives His Call 42 -- Discovering Forgiveness 47 -- Discovering Humility 53 -- Discovering Grace 63 -- Guyon in the Bower of Bliss 69 -- Chapter 4: WHEN CUPID’S MAN COURTS VENUS’ DAUGHTER 73 -- Scudamour’s Calling 74 -- Discovering Chastity: Love as Friendship 79 -- Discovering Chastity: Love as Service 84 -- Discovering Grace 86 -- Scudamour and Amoret 88 -- Chapter 5: SPENSER’S METHOD OF GRACE: THE CONCLUSION 93 -- Works Cited 97.
Keywords: Academic theses; Arthurian romances; European literature--Renaissance; Faerie queene (Spenser, Edmund); Grace (Theology); Spenser, Edmund, 1552?-1599; Theology